Evaluation of the sulphate resistance of foamed concrete containing processed spent bleaching earth - Rokiah, Othman; Khairunisa, Muthusamy; Youventharan, Duraisamy; Mohd Arif, Sulaiman; Ramadhansyah, Putra Jaya; Nadiatul Adilah, Ahmad Abdul Ghanib; Sajjad Ali, Mangi (Taylor & Francis, 2020)
Processed spent bleaching earth (PSBE) is the end product derived from the processing of de-oiled spent bleaching earth (SBE) after the oil is recovered. Bleaching earth is very fine powder clay, and its main component is silicon dioxide used for refining process of palm oil and its by product is known as SBE is commonly disposed to landfill. The bleaching earth that is used for decolouring during the palm oils refining process form a solid sludge called the SBE. The SBE is generated in large quantities and it is becoming increasingly difficult to ignore the disposal of SBE when production of palm oil increases rapidly . Hence , the problem can be overcome by reusing solid waste as construction materials. In this study, the effect of using PSBE as a partial cement replacement in foamed concrete on durability resistance sulphate attack is investigated. Sulphate resistance in terms of expansion, loss in mass and loss in compressive strength after 52 weeks immersed in 5% sodium sulphate was evaluated. On the other hand, the microstructure changes in the specimens were analysed by scanning electron microscopy (SEM), X-ray diffraction (XRD) and thermogravimetry analysis (TGA). Comparisons are made between two mixtures which main ly control foamed concrete (FC) and foamed concrete containing 30% PSBE (PFC). Major findings show that when 30% PSBE added in a concrete mixture, after 52 weeks samples being immersed in 5% sodium sulphate, it will be more durable compared to control specimen (FC). It was recorded that change in mass, in expansion and loss in strength was 1.32%, 0.98% and 7.5% respectively. The microstructure study has confirmed that inclusion of PSBE in foamed concrete is known to improve the internal structure of PFC to be denser than control FC specimen with the visible image of crowded tiny of cotton shaped (CSH) and few hexagonal plates (CH) contributing to enhanced strength and durability. Conclusively, the foamed concrete containing 30% PSBE as partial cement replacement which exhibits enhanced strength and durability than plain foamed concrete has the potential to be used in construction application.